2017
DOI: 10.1007/s10113-017-1247-9
|View full text |Cite|
|
Sign up to set email alerts
|

The Paris Agreement and climate change negotiations: Small Islands, big players

Abstract: Climate change poses an existential threat to Small

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(68 citation statements)
references
References 17 publications
(15 reference statements)
0
53
0
8
Order By: Relevance
“…This will be a difficult task as the world has already experienced around 1°C of anthropogenic global warming to date (Haustein et al, ), although recent work has suggested it may still be achievable (Millar et al, ). Much of the impetus for the 1.5°C global warming target came from small island states concerned about sea level rise (Ourbak & Magnan, ). Here we show that the largest beneficiaries of reduced global warming, with respect to limiting perceptible temperature change, are people living in tropical regions.…”
Section: Mainmentioning
confidence: 99%
“…This will be a difficult task as the world has already experienced around 1°C of anthropogenic global warming to date (Haustein et al, ), although recent work has suggested it may still be achievable (Millar et al, ). Much of the impetus for the 1.5°C global warming target came from small island states concerned about sea level rise (Ourbak & Magnan, ). Here we show that the largest beneficiaries of reduced global warming, with respect to limiting perceptible temperature change, are people living in tropical regions.…”
Section: Mainmentioning
confidence: 99%
“…Paragraph 52 of the Paris Agreement states “… Article 8 of the Agreement does not involve or provide a basis for any liability or compensation.” Nonetheless, the Paris Agreement is still “premised on the concept of differentiated responsibilities” (Lees, , p. 61). This relates to the acknowledgment that nations which have disproportionately benefited from fossil fuel‐based economies have a responsibility to help states that already are and/or are likely to face the most severe L&D, which they have contributed very little toward—SIDS being a case in point throughout the literature (Adelman, ; Hoad, ; Ourbak & Magnan, ). Debate surrounding liability and compensation are framed by several key areas including ethics (31%), law (29%), justice (29%), equity (16%), and human rights (16%), which are all well represented.…”
Section: Resultsmentioning
confidence: 99%
“…Concern about climate change impacts, commencing in the late 1980s, has been channelled into long‐term lobbying in the context of the United Nations Framework Convention on Climate Change (UNFCCC). Pacific Island leaders have made consistent arguments at successive UNFCCC Conferences of the Parties (COP) for global reductions in greenhouse gas emissions, to reduce the risk of sea‐level rise and other climate change impacts (de Agueda Corneloup and Mol, ; Ourbak and Magnan, ). Pacific Island leaders have been instrumental in building a sense of solidarity and alliance between climate‐affected peoples and nations.…”
Section: Indigeneity Mobility and Place In The Pacificmentioning
confidence: 99%